1993
DOI: 10.1111/j.1365-2826.1993.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A: Secretion of Processed Products from the Stimulated Retrogradely Perfused Bovine Adrenal Gland

Abstract: Chromogranin A (CGA) is a member of a family of highly acidic proteins co-stored and co-secreted with adrenaline and noradrenaline in the adrenal medulla. A number of biologically active fragments of CGA (CGAFs) have been characterized including a group of small N-terminal fragments collectively named vasostatins due to their vascular inhibitory activity. In the present study, the release of CGAFs, including CGA N-terminal fragments, from the isolated, retrogradely perfused bovine adrenal gland, has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 26 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…Proteolysis of chromogranin A takes place both within secretory granules and extracellularly, giving rise to several smaller biologically active peptides such as pancreastatin (which inhibits insulin and parathyroid hormone release [21]), ␤-granin or vasostatin (which inhibits parathyroid hormone release and relaxes vascular smooth muscle [22][23][24][25][26]), and parastatin (which inhibits parathyroid hormone release [27]). An emerging functional pattern is that such chromogranin A fragments may inhibit further hormone release from the endocrine cell of origin, perhaps in autocrine, homeostatic (negative feedback) fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolysis of chromogranin A takes place both within secretory granules and extracellularly, giving rise to several smaller biologically active peptides such as pancreastatin (which inhibits insulin and parathyroid hormone release [21]), ␤-granin or vasostatin (which inhibits parathyroid hormone release and relaxes vascular smooth muscle [22][23][24][25][26]), and parastatin (which inhibits parathyroid hormone release [27]). An emerging functional pattern is that such chromogranin A fragments may inhibit further hormone release from the endocrine cell of origin, perhaps in autocrine, homeostatic (negative feedback) fashion.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides include: ( a ) pancreastatin (porcine chromogranin A 240-288 ; 21), originally isolated from porcine pancreas, which inhibits glucose-stimulated insulin release from islet ␤ cells and parathyroid hormone release from chief cells; ( b ) the NH 2 terminus of chromogranin A, termed ␤ -granin (rat chromogranin A 1-114 ; [22][23][24] or vasostatin (human chromogranin A ; 25,26), which inhibits parathyroid hormone release and relaxes vascular smooth muscle; and parastatin (porcine chromogranin A 347-419 ; 27), which inhibits parathyroid hormone release.…”
Section: Introductionmentioning
confidence: 99%
“…results revealed that two of the post-translational modifications on bovine CGA are detected on derived peptides that inhibit hormone and neurotransmitter release: (i) CGA-(1-113) containing phosphorylated Ser 81 corresponds to the vasostatin II sequence (10) and is homologous to pancreatic rat betagranin (9), and (ii) the natural fragment CGA-(347-419) bearing phosphorylated Ser 372 and Ser 376 is parastatin (18). Previously, both CGA and pancreastatin were shown to inhibit low Ca 2ϩ -stimulated parathyroid cell secretion (53,54).…”
Section: Location Of the O-glycosylation And Phosphorylation Sites Onmentioning
confidence: 99%
“…For example, in the N-terminal domain, a peptide corresponding to the sequence 1-113 has been shown to inhibit hormone secretion in the bovine parathyroid gland (8); a homologous peptide, betagranin, corresponding to the sequence 1-115 has been isolated from rat pancreas, but its function has not yet been defined (9). Vasostatins are peptides containing the N-terminal sequence 1-76/113 (10) and have been found to exhibit vasoinhibitory activity of isolated human blood vessels (11,12). As early as 1988, it was established that CGA is the precursor of a peptide that inhibits the secretory activity of chromaffin cells (13).…”
mentioning
confidence: 99%
“…3). These are (i) the vasostatin/fl-granin peptides, comprising the N-terminal 113 amino acids (flgranin/vasostatin II) of CGA and in some tissues (except in rat) a shorter N-terminal 76-amino acid polypeptide (vasostatin I) [91,103,104], (ii) pancreastatin [21,105], (iii) WE-14 [86,106,107] and (iv) the parastatin/GE-25 peptides [88,108,109]. Each of the peptides above have been demonstrated to exist in endocrine tissues by extraction, isolation, purification and peptide sequencing.…”
mentioning
confidence: 99%